Deconstruction of The Korawa Character in The Novel Perang By Putu Wijaya - Fatonah, Khusnul; Rahman, Gohar (Lingua : Journal of Linguistics and Language, 2024)
This research aims to analyze the deconstruction of the Korawa characters in the novel Perang by Putu Wijaya. In the epic Mahabharata, the Korawa are conventionally positioned as antagonistic figures representing evil, while the Pandawa are depicted as symbols of virtue. However, through a deconstructive approach, the novel Perang dismantles this binary opposition and presents a new perspective on the Korawa. This type of research is qualitative, utilizing content analysis and supported by Derrida's deconstruction theory. Data is drawn from quotes in the novel that reveal shifts in meaning, the reconstruction of the Korawa character, and criticism of several narratives that have long been considered absolute. The results of the research show that the Korawa in the novel Perang is not only portrayed as the evil side but also as a group with complex characters, humanitarian values, and perspectives that can be understood. By deconstructing the dichotomy between good and evil, this novel offers a new discourse that history and the identity of characters are not absolute but rather the result of constructions that can be questioned and reinterpreted.